Studies on genotype x environment interactions of sunflower hybrids (Helianthus annuus L.): STUDIES ON GENOTYPE X ENVIRONMENT INTERACTIONS OF SUNFLOWER HYBRIDS - A M LANGHI; S R PATEL; A V NARWADE; R K PATEL; K N CHAUDHARI; H N CHHATROLA (Journal of Oilseeds Research, 2021)
Twenty eight hybrids derived from four CMS lines and seven restorer lines along with two checks were evaluated in randomized block design at three locations for G x E interactions and stability parameters. Stability analysis revealed that genotype x environment interactions were highly significant for all the eleven traits which indicated differential response of genotypes to varied environments. Cross combinations SVCMS-1 x SVSR-3, SVCMS-1 x SVSR-5, SVCMS-2 x SVSR-2, SVCMS-2 x SVSR-4, SVCMS-3 x SVSR-2, SVCMS-3 x SVSR-3, SVCMS-3 x SVSR-7, SVCMS-4 x SVSR-7 and check Phule Raviaj had significantly higher mean than population mean and regression coefficient less than unity which indicated their stable and wide adaptability to poor environment, while, hybrids, viz., SVCMS-1 x SVSR-7, SVCMS-2 x SVSR-3, SVCMS-2 x SVSR-6, SVCMS-3 x SVSR-1, SVCMS-3 x SVSR-4, SVCMS-3 x SVSR-5, SVCMS-3 x SVSR-6, SVCMS-4 x SVSR-1, SVCMS-4 x SVSR-5 SVCMS-4 x SVSR-6 and check LSFH-171 were with high mean, regression coefficient more than unity (bi>1) with non-significant least deviation from regression line indicating their specific adaptation to favorable or rich environments.